Comparative Legal Analysis of the Resolution of Physical Violence Crimes Against Women in Indonesia and Malaysia - Sopacua, Margie Gladies; Taufik, Iqbal; Ablamskyi, Serhii (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
The incidence of criminal acts of violence against women, or gender-based violence, in both Indonesia and Malaysia has shown an upward trend. This study aims to conduct a comparative legal analysis of the resolution mechanisms for physical violence against women in the two countries. The research employs a doctrinal legal method.The findings indicate that in Indonesia, the resolution of physical violence against women involves both penal and non-penal approaches. Domestic violence cases are addressed through multiple strategies, including preemptive, preventive, and curative measures. In Malaysia, the resolution of domestic violence cases includes the issuance of Interim Protection Orders (IPO) and Protection Orders (PO) by the courts, which are accompanied by access to shelters, counseling services, legal advice, guidance, and referrals to relevant institutions.The study concludes that both Indonesia and Malaysia share common objectives in preventing and eradicating domestic violence. However, their approaches differ due to the distinct legal systems each country follows. Malaysia adheres to the Anglo-Saxon common law system, whereas Indonesia follows the Civil Law tradition.